Learning-by-examples techniques as applied to electromagnetics. Issue 4 (4th March 2018) - Massa, A.; Oliveri, G.; Salucci, M.; Anselmi, N.; Rocca, P.
Abstract: There is a wide number of problems in electromagnetic ( EM ) engineering that require a real-time response or in which the input–output relationship is not a-priori known or cannot be defined due to the complexity of the scenario at hand. These issues have induced researchers toward the development and application of Learning-by-Examples ( LBE ) techniques thanks to their extremely high computational efficiency and to their capability to emulate the behavior of complex systems on the basis of a set of collected examples. In this framework, this paper aims to present an overview of the state-of-the-art and recently developed LBE -based strategies as applied to the solution of engineering problems in the field of Electromagnetics. Starting from a general and basic introduction to LBE techniques, the most popular LBE methods used in EM engineering will be re-called. Afterwards, a review on how the LBE methodologies have been applied by various researchers in different application contexts, including among others antennas, microwave circuits, inverse scattering and remote sensing, will be given. Finally, current research trends and envisaged developments are discussed.